2018
DOI: 10.1186/s13018-018-0817-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL17RC and COL6A1 genetic polymorphisms with susceptibility to ossification of the thoracic posterior longitudinal ligament in Chinese patients

Abstract: BackgroundIn our previous whole-genome sequencing study of 30 unrelated northern Chinese Han patients, we identified six single nucleotide polymorphisms (SNPs) in the interleukin 17 receptor C (IL17RC) and collagen type VI α1 chain (COL6A1) genes that were potentially associated with thoracic ossification of the posterior longitudinal ligament (T-OPLL). To determine whether these six SNPs are associated with susceptibility to T-OPLL in the northern Chinese Han population, we performed a case-control associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Despite advances in surgical techniques, the treatment of T-OPLL remains challenging. Previous studies conducted by our group identified the rs201153092A mutation site in the COL6A1 gene as a potentially pathogenic genetic locus for T-OPLL (26,27). The present study revealed the functional impact of the rs201153092A mutation of the COL6A1 gene.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Despite advances in surgical techniques, the treatment of T-OPLL remains challenging. Previous studies conducted by our group identified the rs201153092A mutation site in the COL6A1 gene as a potentially pathogenic genetic locus for T-OPLL (26,27). The present study revealed the functional impact of the rs201153092A mutation of the COL6A1 gene.…”
Section: Discussionsupporting
confidence: 64%
“…However, few studies have assessed the contribution of T-OPLL susceptibility genes. Previous studies have shown that genetic factors may also play an important role in the development of T-OPLL, the rs201153092A mutation site in the collagen 6A1 (COL6A1) gene was identified as a susceptibility locus for T-OPLL (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent whole-genome sequencing study identified that rs199772854 in the IL17 receptor C ( IL17RC) gene is a potentially pathogenic loci for T-OPLL (24). In addition, our case-controlled association study confirmed that this mutation was potentially associated with susceptibility to T-OPLL in individuals of Chinese Han ethnicity (25).…”
Section: Introductionsupporting
confidence: 70%
“…[ 3 7 ] Multiple genetic factors contribute to thoracic OPLL (T-OPLL); rs201153092 and rs13051496 in the COL6A1 gene; and rs199772854, rs76999397, and rs189013166 in the IL17RC gene. [ 8 ] Although T-OPLL typically presents as a slowly progressive condition, up to 10% may become acutely symptomatic from severe spinal cord compression. [ 5 7 ]…”
Section: Discussionmentioning
confidence: 99%